The Use of Learning Media to Improve Student Learning Outcomes at Elementary Schools - Rambe, Juli Asmida; Erika, Erika (LPPPI Publishing, 2025)
Learning media is a tool that can be used by teachers in the learning process to create learning that is interesting and easier to understand in accordance with learning objectives, there are lots of learning media that can be used both from the environment and from factory-made. This article aims to examine the use of appropriate learning media to improve student learning outcomes at the elementary school (SD) level. The type of research used in this research is qualitative research literature review method. The data collection technique uses documentation techniques obtained from various sources which include scientific articles, books and so on which are considered relevant to this research, which are then analyzed using content analysis techniques. The results showed that student learning outcomes were influenced by the use of media in learning, there are many benefits in using learning media, namely learning will be more interesting, the material taught is easier for students to understand.